Income Shocks and Conflict : Evidence from Nigeria - Abidoye, Babatunde; Calì, Massimiliano (World Bank Group, Washington, DC, 2015)
This paper extends the micro evidence on the impact of income shocks on civil conflict using data across Nigerian states over the past decade. The paper uses an innovative empirical strategy matching household survey, oil production, and domestic and international price data to capture three separate channels linking income changes to conflict. Price increases of consumed items have a significant conflict-inducing effect consistent with the hypothesis that they reduce real incomes and thus the opportunity cost of fighting. Failure to include this consumption impact severely biases (toward zero) the conflict-reducing effect of price rises of agricultural commodities via production. In addition, oil price hikes increase conflict intensity in oil producing areas, consistent with the "rapacity" hypothesis. However, this effect disappears in the period after the agreement granting amnesty to militant groups in oil-producing areas. The paper also discusses the importance of factors mediating the impact of the shocks on conflict and a number of policy implications following the analysis. Finally, the empirical strategy is employed to unveil a strong relationship between income shocks and violence in the current Boko Haram conflict. The analysis suggests some policy implications, which may be relevant for the Nigerian context and beyond.